Hexavalent chromium promotes differential binding of CTCF to its cognate sites in Euchromatin. Issue 12 (2nd December 2021) - VonHandorf, Andrew; Zablon, Hesbon A.; Biesiada, Jacek; Zhang, Xiang; Medvedovic, Mario; Puga, Alvaro
ABSTRACT: Hexavalent chromium compounds are well-established respiratory carcinogens to which humans are commonly exposed in industrial and occupational settings. In addition, natural and anthropogenic sources of these compounds contribute to the exposure of global populations through multiple routes, including dermal, ingestion and inhalation that elevate the risk of cancer by largely unresolved mechanisms. Cr(VI) has genotoxic properties that include ternary adduct formation with DNA, increases in DNA damage, mostly by double-strand break formation, and altered transcriptional responses. Our previous work using ATAC-seq showed that CTCF motifs were enriched in Cr(VI)-dependent differentially accessible chromatin, suggesting that CTCF, a key transcription factor responsible for the regulation of the transcriptome, might be a chromium target. To test this hypothesis, we investigated the effect of Cr(VI) treatment on the binding of CTCF to its cognate sites and ensuing changes in transcription-related histone modifications. Differentially bound CTCF sites were enriched by Cr(VI) treatment within transcription-related regions, specifically transcription start sites and upstream genic regions. Functional annotation of the affected genes highlighted biological processes previously associated with Cr(VI) exposure. Notably, we found that differentially bound CTCF sites proximal to the promoters of this subset of genes were frequently associated with the active histone marks H3K27ac, H3K4me3, and H3K36me3, in agreement with the concept that Cr(VI) targets CTCF in euchromatic regions of the genome. Our results support the conclusion that Cr(VI) treatment promotes the differential binding of CTCF to its cognate sites in genes near transcription-active boundaries, targeting these genes for dysregulation. Abstract : uf0001